2021
DOI: 10.21055/0370-1069-2021-1-52-62
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological Situation on Plague in 2020. Forecast of Episootic Activity of Natural Plague Foci in the Russian Federation and Other CIS Countries for 2021

Abstract: The aim of the work was to substantiate the forecast of the epidemiological and epizootiological situation in natural foci of plague in the Russian Federation, countries of the near and far abroad for the year of 2021. Characteristics of the distribution of Yersinia pestis strains of the main subspecies (subspecies pestis) of medieval and antique biovars, Caucasian (ssp. caucasica) and central Asian (ssp. central asiatica) subspecies by 45 natural foci of the CIS countries are presented in the paper. The persi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
6

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 21 publications
0
2
0
6
Order By: Relevance
“…The main subspecies, which is virulent for humans, includes the following biovars: antiqua, medieval, oriental, and possibly also intermedium ( 1 ). Our molecular investigations showed that strains of the phylogenetic branch 2.MED of the medieval biovar occupy about 93.3% of the territory of the natural foci in the Commonwealth of Independent States ( 1 , 2 ). At the end of the 19th century and beginning of the 20th, numerous outbreaks of plague were registered in the Northern Caspian Sea region in Russia and Kazakhstan.…”
Section: Announcementmentioning
confidence: 87%
“…The main subspecies, which is virulent for humans, includes the following biovars: antiqua, medieval, oriental, and possibly also intermedium ( 1 ). Our molecular investigations showed that strains of the phylogenetic branch 2.MED of the medieval biovar occupy about 93.3% of the territory of the natural foci in the Commonwealth of Independent States ( 1 , 2 ). At the end of the 19th century and beginning of the 20th, numerous outbreaks of plague were registered in the Northern Caspian Sea region in Russia and Kazakhstan.…”
Section: Announcementmentioning
confidence: 87%
“…It should be noted, if we take into account the latest data of modern studies, that the area of natural foci with circulation of Y. pestis strains of the Medievalis biovar 2.MED is 221,347 km 2 in gopher type and 1,728,676 km 2 in sandstone type [17], where Y. pestis strains of the phylogenetic branch of the Medievalis biovar 2.MED1 and 2.MED0, respectively, may have been the cause of the above-mentioned outbreaks.…”
Section: Discussionmentioning
confidence: 99%
“…важность получения геномного портрета и изучения направлений эволюции возбудителя этой зоонозной природно-очаговой инфекции, оставившей беспрецедентный след в истории, не вызывает сомнений. из четырех известных биоваров основного подвида возбудителя чумы именно высоковирулентный и эпидемически значимый средневековый биовар Yersinia pestis (2.MED) занимает 93,3 % энзоо тичной по чуме территории очагов стран снг, что составляет 1959965 км 2 [1,2]. согласно данным эпидемиологического и эпизоотологического мониторинга, в конце XIX -начале XX в. в прикаспии происходили массовые вспышки чумы, внутривидовое положение этиологических агентов которых не было установлено.…”
unclassified